SHARING THE APPEAL OF JAPANESE CULTURE WORLDWIDE: A DIGITAL INTERCULTURAL COMMUNICATION PROJECT USING PADLET - Shinji Okumura (PUPIL: International Journal of Teaching, Education and Learning, 2025)
Research Objectives This project explores how digital tools can foster intercultural understanding by enabling Japanese university students to share aspects of their culture with peers abroad. Through content creation and international exchange on Padlet, students not only enhance their communication skills but also gain a renewed appreciation for their cultural heritage. Methodology The project unfolds in three stages: Topic Selection: Students choose themes within Japanese pop culture, such as anime, manga, J-POP, or video games, based on personal interest and familiarity. Research and Framing: Students research the historical and cultural context of their chosen topics, focusing on how to present them in a way that is engaging and accessible to an international audience. Particular attention is paid to cultural nuances and sensitivities. Content Creation and Exchange: Students create bilingual (Japanese-English) presentations using PowerPoint and other visual media, which are shared via Padlet. Partner universities in the U.S. and Australia support distribution. Overseas students respond through comments and likes, enabling interactive dialogue. After the exchange, participants reflect on their experiences through open-ended questionnaires. Findings Student feedback highlighted several key outcomes: One student reported seeing familiar cultural elements in a new light by considering how they might be perceived internationally. Another described a sense of pride and motivation after receiving feedback on the global appeal of kawaii culture. A third student gained more profound respect for the creativity of Japanese content creators during research on anime. Others emphasised the power of visuals to bridge language gaps and support effective communication in English. Research Outcomes The project enhanced students’ intercultural awareness, empathy, and digital communication skills and encouraged a more personal engagement with their own cultural identity. For international learners, the student-created content offered a fresh and relatable perspective on Japanese culture, enriching Japanese language education abroad beyond the confines of standard curricula. Future Scope This initiative demonstrates the potential of digital platforms in intercultural education. Future directions include expanding institutional partnerships, experimenting with new media tools, and incorporating real-time interactions to further deepen cross-cultural engagement.